Effects of cottonseed meal protein hydrolysate on intestinal microbiota of yellow-feather broilers - Zhang, Xiaoyang; Wang, Hailiang; Niu, Yujie; Chen, Cheng; Zhang, Wenju (Frontiers in Microbiology, 2024)
We evaluated the effects of cottonseed meal protein hydrolysate (CPH) on the intestinal microbiota of yellow-feather broilers. We randomly divided 240 chicks into four groups with six replicates: basal diet with 0% (CON), 1% (LCPH), 3% (MCPH), or 5% (HCPH) CPH. The test lasted 63 days and included days 1–21, 22–42, and 43–63 phases. The ACE, Chao1, and Shannon indices in the MCPH and HCPH groups of 42-day-old broilers were higher than those in the CON group (p < 0.05), indicating that the cecum microbial diversity and richness were higher in these groups. Firmicutes and Bacteroidetes were the dominant phyla; however, the main genera varied during the different periods. The abundance of Lactobacillus in CPH treatment groups of 21-day-old broilers was high (p < 0.05); in the 42-day-old broilers, the abundances of Barnesiella, Clostridia_vadinBB60_group, and Parasutterella in the LCPH group, Desulfovibrio, Lactobacillus, Clostridia_vadinBB60_group, and Butyricicoccus in the MCPH group, and Megamonas and Streptococcus in the HCPH group increased; in the 63-day-old broilers, the abundance of Clostridia_UCG-014 and Synergistes in the LCPH and HCPH group, respectively, increased (p < 0.05), and that of Alistipes in the LCPH and MCPH groups decreased (p < 0.05). And changes in the abundance of probiotics were beneficial to improve the intestinal morphology and growth performance. In addition, the LCPH treatment increased the complexity of the microbial network, while the MCPH treatment had the same effect in 42-day-old broilers. Thus, CPH increased the relative abundance of beneficial intestinal microbiota and enhanced the richness and diversity of the bacterial microbiota in broilers aged <42 days; this effect was weakened after 42 days.